Gwarancje konstytucjnego prawa do nauki w szkole niepublicznej - Trybka, Wiktor (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The right to education is one of the most important human rights. In other words, the right to education is the each of us right to use the educational services provided by both public and private entities. The legal situation of the beneficiary of educational services is regulated by administrative and civil law. The principle of free and compulsory education at the basic level has been widely accepted in Polish law. Education up to the age of 18 is obligatory. Implementation of the constitutional right to education takes place as part of the provision of services by public and non-public schools. Non-public schools have the same duties related to the education of pupils as public schools, on the other hand, students of public and private schools enjoy the same rights. The fulfillment of administrative and legal obligations by non-public schools remains under the constant supervision of competent public administration authorities.
Keywords: administrative law; non-public school; school obligation; administrative proceedings; right to education